Exploring the color of plant powders using computer colorimetry - Niemirich, Alexandra; Petrusha, Oksana; Vasheka, Oksana; Trofymchuk, Lyudmila; Myndrul, Natalia (Eastern-European Journal of Enterprise Technologies, 2016)
The question of using a new method of color measurement with the use of contemporary digital computer technology was considered, which implies obtaining, under certain conditions, digital image of the tested sample. The plant powders, explored in the work, contain a number of pigments, which determine both the color of the powder and the color of culinary products, in composition of which they are included. When measuring сolor coordinates of the powders, their restoration with water was conducted, in this case, the restored samples have lower lightness in comparison with the native powder. The difference of change in the value of сolor coordinate L on average decreases by 20 %. The measurement of сolor of prepared meals, which was made with the use of plant powders, showed that they have lower saturation in comparison with the powders, since the pigment concentration decreases. In this case, other ingredients of meals shift the magnitudes of сolor coordinates of lower magnitudes of saturation and lightness towards the lightness of native powder. The exception is the powder from sea buckthorn, the pigments of which are manifested poorly in the restored state. The accessibility of the method makes it possible to use it for evaluating quality, controlling technological process of preparing meals and culinary products using traditional and innovative ingredients, including vegetable and fruitandberry powders.